A Dendrophyllia ramea Population in the Ionian Sea (Central Mediterranean Sea) Threatened by Anthropogenic Impacts - Angiolillo, Michela; Giusti, Michela; Rossi, Lorenzo; Tunesi, Leonardo (Frontiers in Marine Science, 2022)
This study reports the first attempt to quantitatively describe a Dendrophyllia ramea population on the Apollo bank (Ionian Sea), revealed in summer 2021 through a remotely operated vehicle (ROV) survey. The habitat description, bathymetric distribution, population density and structure of the species were assessed by image analysis. A well-developed population of D. ramea, located on boulders on a sedimentary plateau at 70–80 m depth, was observed. The density ranged on average between 0.17 ± 0.04 and 0.8 ± 2.4 colonies m−2 with dense patches up to 8 colonies m−2. The population consisted primarily of many isolated single corallites and colonies of various sizes, some of which reached a maximum height of more than 40 cm. Deep-water fishing activities, primarily longline fishing, negatively affected this species. The new collected data add knowledge about this vulnerable scleractinian coral. The documented negative effect of fishing activities on vulnerable marine ecosystem (VME) species further highlights the need for urgent conservation measures.